One-stop stroke management platform reduces workflow times in patients receiving mechanical thrombectomy - Zhou, Tengfei; Li, Tianxiao; Zhu, Liangfu; Li, Zhaoshuo; Li, Qiang; Wang, Ziliang; Wu, Liheng; He, Yingkun; Li, Yucheng; Zhou, Zhilong; Guan, Min; Ma, Zhenkai; et al. (Frontiers in Neurology, 2023)
Background and purpose: Clinical outcome in patients received thrombectomy treatment is time-dependent. The purpose of this study was to evaluate the efficacy of a one-stop stroke management (OSSM) platform in reducing in-hospital workflow times in patients receiving thrombectomy compared with the traditional model. Methods: The data of patients who received thrombectomy treatment through the OSSM platform and traditional protocol transshipment pathway were retrospectively analyzed and compared. The treatment-related time interval and the clinical outcome of the two groups were also assessed and compared. The primary efficacy endpoint was the time from door to groin puncture (DPT). Results: There were 196 patients in the OSSM group and 210 patients in the control group, in which they were treated by the traditional approach. The mean DPT was significantly shorter in the OSSM group than in the control group (76 vs 122 min; P < 0.001). The percentages of good clinical outcome at the 90-day time point of the two groups were comparable (P = 0.110). A number of 121 patients in the OSSM group and 124 patients in the control group arrived at hospital within 360 min from symptom onset. The mean DPT and time from symptom onset to recanalization (ORT) were significantly shorter in the OSSM group than in the control group. Finally, a higher rate of good functional outcome was achieved in the OSSM group than in the control group (53.71% vs 40.32% P = 0.036). Conclusions: Compared to the traditional transfer model, the OSSM transfer model significantly reduced the in-hospital delay in acute stroke patients receiving thrombectomy treatment. This novel model significantly improved the clinical outcomes of patients presenting within the first six hours after symptoms onset.